Reimagining Black Art and Criminology : A New Criminological Imagination - Glynn, Martin, 1957- (Book collections on Project MUSE., 2021)
Martin Glynn explores the relevance black artistic contributions have for understanding crime and justice. Through art forms including black crime fiction, black theatre and black music, this book brings attention to marginalized perspectives within mainstream criminology.